Penatalaksanaan Fisioterapi Pada Bell’s Palsy Dextra di Klinik Mulyosari Surabaya: A Case Report - Rozamala Ma’arij; Yasin Galih (Nur Science Institute, 2022)
Bell's palsy Bell's Palsy is weakness or paralysis of the peripheral facial nerves, acute in nature, and the cause is unknown (idiopathic). Bell's Palsy often occurs in some people due to exposure to wind, cooling or air conditioning and also due to viruses. The annual incidence of bell's palsy is between 11.5 and 40.2 cases for 100,000 people. A 45-year-old male patient who works as an office worker came to the Mulyosari Physiotherapy Clinic in Surabaya on February 18, 2021 from a neurologist's referral with a diagnosis of right facial weakness. Patients work in the office every day using air conditioning. The incident occurred when waking up, the patient felt pain behind the ear then the patient found it difficult to blink and stood in front of the mirror seeing that his side face was not symmetrical, his lips and eyebrows were not symmetrical and his eyes were difficult to blink. The evaluation results for 6 times of therapy by receiving therapy three times a week, it was found that there was an increase with the administration of Infrared (IR) modalities, Electrical Stimulation (ES), and Facial Massage. Measurements with the MMT scale and the Ugo Fisch scale were used to measure fascial strength and functional ability, as well as the final evaluation. The recovery process takes a fairly fast time if handled directly and routinely. It is very important to do physiotherapy as early as possible to improve circulation, increase facial muscle strength and facial functional abilities so as to prevent more chronic problems and increase patient confidence as before.